PERANCANGAN DESAIN INTERIOR ACARAKI JAMU EXPERIENCE CENTER DI JAKARTA PUSAT DENGAN PENDEKATAN KONSEP LOKAPALA FILOSOFI JAMU - Amalia, Fatharani; Kurniawan, Rizki; Sutapa, Widasapta (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2024)
Preserving herbal medicine drinking among young people to maintain health is of course a strategic step so that the existence of herbal medicine is not eroded by time. The bitter taste, the decrease in herbal medicine sellers passing in front of the house, and the assumption that herbal medicine is an old or ancient drink, are some of the reasons why young people are starting to abandon the habit of drinking herbal medicine. This is also supported by a lack of literacy about the history and benefits of herbal medicine, which is a cultural heritage that today's young people should be proud of, like the habit of spending time hanging out in coffee shops. Seeing the many coffee shops that are innovating in terms of presentation and marketing, this has led to business actors like Selamatki creating modern herbal medicine shops like coffee shops that can be used as gathering places. So that current problems can be accepted by young people, of course designing the interior of a herbal medicine shop must be adapted to the interests of today's young people. By presenting a contemporary atmosphere, a new experience in enjoying herbal medicine when gathered, the interior design of the new Caraki cafe can be used as a new facility for recreation and education that can be visited by all groups. The interior design of the Caraki cafe uses the Lokapala concept, which in Sanskrit means "Guardian of the World". Lokapala represents the protection and preservation of ancient herbal wisdom, as well as maintaining the balance of the human body from surrounding disease disorders.